Does God Intend that Sin Occur? - Hart, Matthew J.; Hill, Daniel J.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This open access book argues, from a detailed consideration of the Christian Scriptures, that God intends that sin occur. It swims against the tide of current thinking in philosophy of religion, arguing for an unfashionable conclusion. The book begins by considering the history of views on the question, paying particular attention to the Reformed or Calvinistic tradition. The heart of the book is a detailed examination of key passages from the Christian Scriptures that, it is argued, show that God does intend that sin occur. It also discusses in detail two alternative views that could be used to reinterpret these texts, one view that God intends only that the substratum of the sinful action occur, not the sin itself, and the other that God acts because a sin will occur but not intending that that sin occur. The book argues that these interpretative strategies, even when combined together, do not produce a plausible interpretationof the texts adduced. Dr Matthew J Hart recently acquired a PhD in philosophy from the University of Liverpool. He has publications in such journals as Disputatio, Philosophia Christi, and The European Journal for the Philosophy of Religion. Dr Daniel J Hill has taught in the Department of Philosophy at the University of Liverpool since 2000. He is author of Divinity and Maximal Greatness, and co-author of Christian Philosophy: A-Z and The Right to Wear Religious Symbols. He is also the Chair of the Tyndale Fellowship$1 (Bs Study Group in Philosophy of Religion.s
Chapter 1: Introduction and Historical Overview -- Chapter 2: Interpreting the Scriptures -- Chapter 3: Triple Effect -- Chapter 4: The Substratum strategy -- Chapter 5: Assessing Interpretative Strategies -- Chapter 6: Passages from the Old Testament (Hebrew Scriptures) -- Chapter 7: Passages from the New Testament -- Chapter 8: Objections and Concerns.
Keywords: Religion -- Philosophy; Ethics; Philosophy of Religion; Moral Philosophy and Applied Ethics